IMPLEMENTASI METODE FIXED PERIOD REQUIREMENT DAN LEAST UNIT COST DALAM MATERIAL REQUIREMENT PLANNING (MRP) UNTUK KOMPONEN SKIN D-NOSE AIRBUS A350 - Setianto, Nasrul; Arianty Syamsi, Wuri; Ihsan, Tiaradia (CV SWA Anugerah, 2025)
This study focuses on evaluating the efficiency of managing raw material inventory with the Material Requirements Planning (MRP) method to reduce inventory costs at PT DXI.This research method was carried out using quantitative methods with the data source used being secondary data through historical company demand data. The MRP method in the research is applied to identify raw material needs based on historical demand data, calculate optimal ordering schedules, and evaluate the impact on inventory costs. The Lot Sizing technique used in this MRP method is Fixed Period Requirement and Least Unit Cost. Research findings indicate that implementing the MRP Lot Sizing method significantly reduces inventory costs. The aviation manufacturing sector benefits greatly from this study, particularly within supply chain management, demonstrates significant efficiency improvements, which is intricate and ever-changing. It is envisaged that using this approach will help with attempts to keep a sustainable supply of components and optimize the production process.